ENTREPRENEURIAL ORIENTATION AND ORGANISATIONAL PERFORMANCE; MEDIATION BY ORGANISATIONAL RESILIENCE - Arshad Iqbal; Dr Shazia Hassan; Dr Muhammad Zia Ur Rehman (International Journal of Contemporary Issues in Social Sciences, 2024)
Strategic management and entrepreneurship literature suggests a significantly positive relationship between that entrepreneurial orientation (EO) and organizational performance (OP). However, the relationship especially in uncertain, ambiguous and dynamic environment is not that straight forward. The relationship is effected by number of intervening and contextual mechanisms. Organisational resilience (OR) being one such mechanism is missing in empirical research exploring the EO and OP relationship. It has been reported that sound planning and suitable adaptive capacities of an organization (organizational resilience) positively affect the organizational performance. Primary purpose of this paper is to investigate the relationship between EO and OP in the developing economy’s context. Additionally it is intended to explore the role of OR as intervening mechanisms impacting the relationship. A casual cross sectional study in developing economies context deploying novel combination of social media networks (SMNs) and direct approaches. Data was collected from a sample 151 managers conversant with the strategic orientation and planning processes of their enterprises, through questionnaire survey. Aligned with previous research findings, the results revealed significant positive relationship between EO and OP. Moreover, it was found that OR partially mediated the association between EO and OP. Hence, hypotheses stands supported. Implications, limitations and direction for future research are discusses.